23 things they don't tell you about capitalism - Chang, Ha-Joon (Penguin Books, 2011)
Challenges popular misconceptions while making startling revelations about free-market practices, explaining the author's views on global capitalism dynamics while making recommendations for reshaping capitalism to humane ends.